Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Arbaminch University - International Livestock Research Institute; Arbaminch University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Arbaminch University. On September 22, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Damtew Darza, President of Arbaminch University.